1990
DOI: 10.1136/adc.65.6.602
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight specific trends in cerebral palsy.

Abstract: A register of infants with cerebral palsy born to mothers resident in the Mersey region from 1967-84 has been maintained using various sources of information. A total of 1056 patients are registered of whom 331 (31%) have hemiplegia or mixed hemiplegia, 236 (22%) have diplegias or mixed diplegia, and 369 (35%) have quadriplegia or mixed quad-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(87 citation statements)
references
References 25 publications
4
78
0
5
Order By: Relevance
“…As Kapoor et al and others also found no association with the parental age. 6,7,10,12 As per their living area no specific pattern of CP with rural 27(58.69%) or urban 19 (41.31%) background was found in review of literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As Kapoor et al and others also found no association with the parental age. 6,7,10,12 As per their living area no specific pattern of CP with rural 27(58.69%) or urban 19 (41.31%) background was found in review of literature.…”
Section: Discussionmentioning
confidence: 99%
“…17 This is in contrast to a couple of other studies which have shown significant association between LSCS and cerebral palsy. 7,19 There was significant history of prolonged labour in 9 (19.56%) and birth asphyxia was 31 (67.39%) patients. Torfs et al, Blair et al, Sharma et al, Suanand et al and others found similar higher risk up to 53 % of CP in Birth asphyxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development and use of neonatal intensive care units throughout Europe and the associated decrease in neonatal mortality in most countries during the 1970s, 1980s, and 1990s, more of these vulnerable babies are surviving (McCormick 1993). There was some evidence of a rise in CP rates among low-birthweight babies during the 1970s and 1980s (Hagberg et al 1989, Pharoah et al 1990, Topp et al 1997a) but the trends in recent years have been less clear (Meberg and Broch 1995, Hagberg et al 1996, Pharoah et al 1998). There has also been concern that the level of severity of disability may be increasing among children with CP (Stanley 1992, Uldall et al 1995, Hagberg et al 1996, Pharoah et al 1996.…”
mentioning
confidence: 99%